2010
DOI: 10.1039/b920608f
|View full text |Cite
|
Sign up to set email alerts
|

“Annular Ring” microtubes formed by SDS@2β-CD complexes in aqueous solution

Abstract: Traditional aqueous self-assembly of tubular structures (as well as other aggregates) usually relies on the hydrophobic effect, a relatively weak and nondirectional interaction. The resultant aggregates are inherently soft, fluid, and less-ordered. Alternatively, we report a novel kind of nonamphiphilic selfassembly of microtubes in aqueous solutions of cyclodextrin/ionic surfactant (CD/IS) complexes. This self-assembly is driven exclusively by H-bonds, relatively strong, directional interactions. The CD/IS mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
131
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 29 publications
(2 reference statements)
6
131
0
Order By: Relevance
“…The molecular self-assembly is formed by sodium dodecyl sulfate (SDS) and β-cyclodextrin (β-CD) through host-guest interactions, which is a good buildingblock for responsive molecular devices and bio-mimic structures. 42,49 β-CD forms a cup shape structure, with one of the rim narrower than the other (SI Fig. S2).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The molecular self-assembly is formed by sodium dodecyl sulfate (SDS) and β-cyclodextrin (β-CD) through host-guest interactions, which is a good buildingblock for responsive molecular devices and bio-mimic structures. 42,49 β-CD forms a cup shape structure, with one of the rim narrower than the other (SI Fig. S2).…”
Section: Figurementioning
confidence: 99%
“…Using this code, we can differentiate domains with various molecular conformations, which would otherwise be difficult to distinguish using optical imaging techniques 41 or homodyne VSFG microscopes. [4][5][6][7][8][9][10][11][12] We implemented this phase-stable collinear HD VSFG microscope to study a guest-host molecular self-assembly 42 spin-coated on gold. We found that the self-assembly contains non-centrosymmetric domains at sizes from about 20 to 100 μm 2 , and there are mainly two types of domains, which have opposite molecular alignment relative to each other.…”
mentioning
confidence: 99%
“…18 Our previous work has shown that they act as facile and versatile templates in the construction of helical and other new colloidal structures by the incorporation of non-magnetic spherical and anisotropic colloids as reported in ref. 18 Our previous work has shown that they act as facile and versatile templates in the construction of helical and other new colloidal structures by the incorporation of non-magnetic spherical and anisotropic colloids as reported in ref.…”
Section: Introductionmentioning
confidence: 93%
“…In these systems, the hydrophobic effect between building blocks was still the main driving forces for the aggregate formation. Recently, Huang et al observed an interesting soft aggregate formation from the fully hydrophilic complexes between an ionic surfactant (SDS) and ␤-CD [19][20][21]. The SDS@2␤-CD complex could self-assemble into lamellaes, microtubes, and vesicles at different concentrations in aqueous systems.…”
Section: Introductionmentioning
confidence: 97%